2011
DOI: 10.3201/eid1703.101410
|View full text |Cite
|
Sign up to set email alerts
|

Novel Picornavirus in Turkey Poults with Hepatitis, California, USA

Abstract: To identify a candidate etiologic agent for turkey viral hepatitis, we analyzed samples from diseased turkey poults from 8 commercial flocks in California, USA, that were collected during 2008–2010. High-throughput pyrosequencing of RNA from livers of poults with turkey viral hepatitis (TVH) revealed picornavirus sequences. Subsequent cloning of the ≈9-kb genome showed an organization similar to that of picornaviruses with conservation of motifs within the P1, P2, and P3 genome regions, but also unique feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 26 publications
3
55
0
1
Order By: Relevance
“…2). At nt positions 558 to 620 (domain J), 559 to 613 (domain J), 559 to 613 (domain J), and 672 to 702 (domain L and the 3=-end pyrimidine-rich region) OHuV-1 had 84%, 84%, 86%, and 100% nucleotide identity to Ljungan virus 1 (EF202833), foot-and-mouth disease virus SAT 1 (HM067706), bovine rhinitis A virus 2 (JN936206), and human cosavirus B1 (FJ438907) (3,12,14). The apical 22 nucleotides in domain D of hungaroviruses are completely identical to Ljungan virus 4 (EU854568) nt 2 to 23 (Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…2). At nt positions 558 to 620 (domain J), 559 to 613 (domain J), 559 to 613 (domain J), and 672 to 702 (domain L and the 3=-end pyrimidine-rich region) OHuV-1 had 84%, 84%, 86%, and 100% nucleotide identity to Ljungan virus 1 (EF202833), foot-and-mouth disease virus SAT 1 (HM067706), bovine rhinitis A virus 2 (JN936206), and human cosavirus B1 (FJ438907) (3,12,14). The apical 22 nucleotides in domain D of hungaroviruses are completely identical to Ljungan virus 4 (EU854568) nt 2 to 23 (Fig.…”
Section: Figmentioning
confidence: 99%
“…In the last few years, there has been a surge in the number of novel picornaviruses discovered and genomes sequenced (4,13,14,15,17,23,33). In 2008, a novel picornavirus (porcine kobuvirus) was serendipitously identified by our laboratory from domestic pigs (25).…”
mentioning
confidence: 99%
“…They bind directly to the ribosome and mediate initiation without the involvement of eukaryotic initiation factors (eIFs) (61,88). The second IRES class is epitomized by the ϳ330-nt-long IRESs of hepatitis C virus (HCV) and pestiviruses (designated HP) (47) and includes structurally related HPlike IRESs that occur in numerous picornaviruses, including porcine kobuvirus (PKV), a member of the Kobuvirus genus, members of the Teschovirus, Sapelovirus, Senecavirus, Tremovirus, and Avihepatovirus genera of Picornaviridae, seal picornavirus 1, and turkey hepatitis virus (8,14,21,26,35,37,73). The presence of related IRESs in unrelated viruses suggests that these elements have been exchanged by recombination (21).…”
mentioning
confidence: 99%
“…Honkavuori et al (2008) discovered two strains of a novel Borna viruses in psittacine birds with proventriculus dilatation syndrome (PDS) characterised by gastrointestinal dysfunction and neurological signs. To identify a candidate of etiologic agent for turkey viral hepatitis (TVH), Honkavuori et al (2011) reported picornavirus in liver samples from diseased turkey poults. Fulminating disease (X disease) of guinea fowl is acute enteritis characterised by intense prostration and a very high mortality.…”
Section: Virus Discovery and Viral Metagenomicsmentioning
confidence: 99%